2008
DOI: 10.1021/ja803482h
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Formation and Decomposition on Atomic Oxygen Precovered Au(111)

Abstract: The carbonate formation and decomposition (CO 3 T CO 2 + O a ) reaction on gold is important from the point of view of lowtemperature CO oxidation. Carbonate formation has been proposed as a possible reaction intermediate in CO oxidation in several investigations of supported and unsupported gold clusters. [1][2][3][4] Therefore, an understanding of this reaction on Au(111) may provide additional insight. Carbonate formation and decomposition went undetected in previous studies on Au (110) 5 and Au(111). 6 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 22 publications
4
69
0
1
Order By: Relevance
“…The overall reaction is calculated to be exothermic by 137.11 kcal mol -1 . For low-temperature CO oxidation, it is generally agreed that carbonate species are an important intermediate [58]. Several investigations have observed its formation on supported and unsupported gold clusters [57][58][59][60][61].…”
Section: Complexes Of Au 2 -And Auag -With O 2 and Comentioning
confidence: 99%
“…The overall reaction is calculated to be exothermic by 137.11 kcal mol -1 . For low-temperature CO oxidation, it is generally agreed that carbonate species are an important intermediate [58]. Several investigations have observed its formation on supported and unsupported gold clusters [57][58][59][60][61].…”
Section: Complexes Of Au 2 -And Auag -With O 2 and Comentioning
confidence: 99%
“…In heterogeneous catalysis, it has been shown that the presence of water increases the observed rate of CO oxidation [9,10]. The degree of rate enhancement depends on the type of support used.…”
mentioning
confidence: 99%
“…Experimental results supported by DFT calculations show carbonate formation and reaction on atomic oxygen precovered Au(111) [39]. Oxygen mixing was observed when 16 O ads precovered Au(111) was exposed to isotopically labelled CO 2 (C 18 O 2 ) at surface temperatures ranging from 77-400 K and initial oxygen coverages ranging from 0.18-2.1 ML.…”
Section: Co Oxidationmentioning
confidence: 73%
“…Mullins and co-workers studied carbonate formation on Au(111) [38][39]. Experimental results supported by DFT calculations show carbonate formation and reaction on atomic oxygen precovered Au(111) [39].…”
Section: Co Oxidationmentioning
confidence: 94%